THE CULTURAL VALUES OF FIGURATIVE LANGUAGE USED IN THE TEXT "PURANJANA BECOMES A WOMAN IN THE NEXT LIFE" - Ni Ketut Dewi Yulianti; I Gst Ayu P. Jesika Sita Devi N (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2022)
This paper aims to analyze the figurative language used in the text Puranjana Becomes Woman in The Next Life. In addition, the cultural values conveyed by the figurative language will also be presented. It will be significant for those engaged in the figure of speech and those who love to use figurative language in their performances. This study needs to be researched because it is a religious text with the figurative language of their cultural values. The meanings of the figurative language must be distinct from the text's theme, which is in line with the cultural values of the text. The data about figurative languages are collected through library research and analyzed based on semantic theory and cultural elements since cultural elements are needed to reveal the cultural values of the text. In this study, the cultural elements are limited to custom and tradition. This paper will provide an understanding of a religious text, specifically in relation to cultural value. Besides, this paper can contribute to the education world and help people gain insight into cultural values from a religious text.